2014
DOI: 10.1103/physrevlett.113.261601
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Hydrodynamics to Nonequilibrium Degrees of Freedom in Strongly Interacting Quark-Gluon Plasma

Abstract: Relativistic hydrodynamics simulations of quark-gluon plasma play a pivotal role in our understanding of heavy ion collisions at RHIC and LHC. They are based on a phenomenological description due to Müller, Israel, Stewart (MIS) and others, which incorporates viscous effects and ensures a well-posed initial value problem. Focusing on the case of conformal plasma we propose a generalization which includes, in addition, the dynamics of the least damped far-from-equilibrium degree of freedom found in strongly cou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(115 citation statements)
references
References 30 publications
(53 reference statements)
3
112
0
Order By: Relevance
“…Specifically, the first-order viscous correction is found to retain the memory of the initial condition. Within a strong coupling calculation, a proper treatment of the underlying microscopic degrees of freedom leads to an evolution equation which is second-order rather than first-order [55], so that the solution is not solely determined by the initial value of T μν . Our calculation provides an explicit illustration, within a weak-coupling calculation, that the initial value of T μν does not solely determine the evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the first-order viscous correction is found to retain the memory of the initial condition. Within a strong coupling calculation, a proper treatment of the underlying microscopic degrees of freedom leads to an evolution equation which is second-order rather than first-order [55], so that the solution is not solely determined by the initial value of T μν . Our calculation provides an explicit illustration, within a weak-coupling calculation, that the initial value of T μν does not solely determine the evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. [144] has recently proposed a way to describe the approach towards hydrodynamics in strongly-coupled SYM that involves equations of motion that are qualitatively different than those in (6.3) and (6.4) since they involve a second order, homogeneous differential equation for the part of the shear stress tensor associated with the two lowest quasinormal modes π are not taken into account). It would be interesting to investigate whether their effective theory is also applicable in the case of the non-conformal plasma studied in this paper.…”
Section: Jhep02(2015)051mentioning
confidence: 99%
“…For different strongly coupled theories it has been shown that the hydrodynamical gradient series expansion has zero radius of convergence and thus, it diverges [19]. On the other hand, the divergent behavior of the hydrodynamical series expansion is also well known in weakly coupled systems based on the Boltzmann equation for relativistic and nonrelativistic systems [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…1D nonautonomous parametrized by a new time w) due to scaling symmetry [19,25]. This suggests that its attractor is a planar 1-manifold characterized by w and the basin of attraction is indeed 2D.…”
mentioning
confidence: 99%